(untitled) (Research, Society and Development, 2021)
To report the construction of health technologies aimed at professionals about the manipulation of bodies in the context of the new coronavirus. This is an experience report, of a descriptive character, based on the analysis and description of the development of health technologies, which aimed to democratize information about care with suspected or confirmed cases of Covid-19 that had evolved to death . The study was based on the reading of the protocol “Body Management of the New Coronavirus”, made available by the Ministry of Health of Brazil and occurred in 5 stages: 1) Situational diagnosis; 2) Literature review; 3) Elaboration of the proposal; 4) Construction of technologies and 5) Implementation of technology. Therefore, the main results of this research are the construction of three health technologies: One in the form of a booklet of size 33 by 19 cm, distributed to professionals, two flowcharts distributed in hospitals and a media in the form of a 1min video. 20s, shared on social networks and multiplatform messaging application. Finally, there was the implementation of these instruments, from the dissemination of the media to health professionals and the professional community. It was concluded in this work that linking the two aspects of education and health requires professional aptitude so that the information reaches the intended audience, therefore, the proposed technologies obtained a positive effect in the community from their dissemination in the digital environment. In addition, the need to build technologies that contribute to clarify and face, with less damage, the new global epidemics, is highlighted.